2007
DOI: 10.1161/01.atv.0000253906.19648.ac
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Activity, Coagulation, and Fibrinolysis During Exercise in Healthy Males

Abstract: Background-Relationships between exercise-induced activation of platelets, blood coagulation, and fibrinolysis, and the importance of thrombin for responses to exercise are not clear. Methods and Results-Effects of thrombin inhibition on hemostatic parameters were examined in a double-blind crossover study comparing the direct thrombin inhibitor argatroban (350 g/kg intravenous bolus followed by 25 g/kg per minute of infusion), the indirect thrombin inhibitor enoxaparin (0.75 mg/kg, intravenous bolus), or plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 30 publications
(43 reference statements)
2
28
0
Order By: Relevance
“…Exercise augments coagulation and fibrinolysis while maintaining the balance in the two processes (Li, He, Blomback, & Hjemdahl, 2007). Exercise has been shown to increase circulating activated platelets (Li et al) and the change is partially explained by an increase in platelet counts induced by exercise (Ahmadizad, El-Sayed, & Maclaren, 2006;Aldemir & Kilic, 2005).…”
Section: Design-randomized Clinical Trialmentioning
confidence: 99%
“…Exercise augments coagulation and fibrinolysis while maintaining the balance in the two processes (Li, He, Blomback, & Hjemdahl, 2007). Exercise has been shown to increase circulating activated platelets (Li et al) and the change is partially explained by an increase in platelet counts induced by exercise (Ahmadizad, El-Sayed, & Maclaren, 2006;Aldemir & Kilic, 2005).…”
Section: Design-randomized Clinical Trialmentioning
confidence: 99%
“…In another study, colon and colleagues (1997 ) reported increased catabolism of fibrinogen and plasminogen looking physically strenuous activity but did not observe significant changes in PT ( 14 ). Naylyn ( 2007) With Survey Platelet activity, coagulation and fibrinolysis during exercise in healthy men exercise increases the concentration of platelets and leukocytes were observed independent of coagulation and fibrinolysis by thrombin is increased but the balance between the sport seems to be maintained ( 26 ). Quinn (2009) stated fibrinolytic activity in postmenopausal women could be improved by 3 weeks of regular training programs under the maximum (21).. Madarameh et al (2010 ) concluded after exercise any of the variables prothrombin complex thrombin -antithrombin 3 and D.Dimer type did not change significantly ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the beneficial effects of exercise (PiePoli et al, 2004;Bassuk and Manson, 2005;Roberts and Barnard, 2005), several studies have found that exercise may induce damaging effects such as acute coronary syndrome (Willich et al, 1993), increased platelet and leukocyte activations, elevated platelet-leukocyte aggregations, and facilitation of thrombogenesis (Li et al, 2007). Additionally, exercise may cause increased stress-induced shear force, and promote platelet and coagulation system activation, catecholamine release (Ikarugi et al, 1999).…”
Section: Introductionmentioning
confidence: 99%